Variación del momento de diseño según los códigos CCP-95 y CCP-14 para puentes simplemente apoyados tipo losa y vigas (2019)
Continuous research, technological and scientific advances lead to the continuous updating of design parameters and regulations of the different fields of civil engineering, the bridges have had various changes in their design and construction methodology. This document seeks to assess the impact on the variation of the live load on bridges simply supported between the last two design codes established in Colombia, the Colombian Code of Seismic Design of Bridges CCP-95 that was used in 2012 and the new Code Colombian of Seismic Design of Bridges CCP-14 performing the calculation of beams for simply supported bridges of different lights and with variable road widths, in order to determine amounts of reinforcement in the cantilever, the plate between beams, the external beam and compare the influence it has on these elements.